PENINGKATAN MOTIVASI BERWIRAUSAHA DAN PERBAIKAN WEBSITE SEBAGAI USAHA MENDORONG KEMAJUAN USAHA BAGI CALON WIRAUSAHAWAN DISABILITAS DI SUMATRA BARAT - Dessy Kurnia Sari; Donard Games; Laura Amelia Triani; Wardah Awwalin Ikhsaniah Saldi; Novi Annisa; Giantina Veronika (BULETIN ILMIAH NAGARI MEMBANGUN, 2024)
This community service aims to motivate and provide understanding to prospective entrepreneurs and entrepreneurs with disabilities regarding entrepreneurial motivation and marketing skills. The use of digital media such as websites and social media to market products is the main agenda in this activity. The urgency of this activity arises from the need for increased marketing of products by entrepreneurs with disabilities who must be skilled at attracting the interest of potential buyers. This activity involves lecturers and students from the Faculty of Economics and Business Universitas Andalas, website experts and content creators. The training was attended by 25 entrepreneurs and prospective entrepreneurs with disabilities with the aim of increasing their business motivation. It was held in Padang, West Sumatra. The training method is carried out by providing motivation at the start of the activity, followed by focus group discussions to accommodate aspirations regarding their needs and obstacles in market access, practice of making websites and social media. The results obtained are stronger business motivation and improving ability of entrepreneurs with disabilities so that they are able to offer products to a wider market. Entrepreneurs with disability consider this activity fits their needs. The participants ready to make their website and social media to be more marketable. This training shows that digitalization can open up market opportunities for entrepreneurs with disabilities who are equipped with knowledge related to managing websites and social media to attract consumer interest. Entrepreneurs with disabilities need to get support from various parties to achieve sustainable economic independence.